2005
DOI: 10.1007/s10534-004-1960-y
|View full text |Cite
|
Sign up to set email alerts
|

Time dependent study to evaluate the efficacy of zinc on hepatic marker enzymes and elemental profile in serum and liver of protein deficient rats

Abstract: This study was designed to determine the time dependent protective effects of zinc sulfate on the serum and liver marker enzymes along with elemental profile in protein deficient Sprague Dawley (S.D.) female rats. Zinc sulfate in the dose of 227 mg/l in drinking water was administered to normal control as well as protein deficient rats for a total duration of 8 weeks. The effects of different treatments were studied on enzymes like alkaline phosphatase (ALP), aspartate aminotransferases (AST) and alanine amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
(29 reference statements)
3
5
0
Order By: Relevance
“…A prolonged Zn treatment almost normalized the Zn balance leading to increased SOD and GPX activity in control and infected animals. Our results are in a good agreement with those of Sidhu et al (2005) who established protective effects of Zn. These authors have studied the effects of Zn supplementation on antioxidant enzymes CAT, GPX, GR, and SOD in rat liver.…”
Section: Discussionsupporting
confidence: 91%
“…A prolonged Zn treatment almost normalized the Zn balance leading to increased SOD and GPX activity in control and infected animals. Our results are in a good agreement with those of Sidhu et al (2005) who established protective effects of Zn. These authors have studied the effects of Zn supplementation on antioxidant enzymes CAT, GPX, GR, and SOD in rat liver.…”
Section: Discussionsupporting
confidence: 91%
“…This may be due to the ability of zinc to compete with arsenic absorption at the intestinal levels, leading to its later retention. This has been depicted in the previous studies which illustrate the ability of zinc to inhibit the uptake of heavy metals like cadmium and nickel [41,42]. On the other hand, zinc levels were significantly down in the liver of arsenic-treated rats, which further supports the accumulation of arsenic and lower levels of metallothionein.…”
Section: Discussionsupporting
confidence: 62%
“…In the absence of infection, the impact of protein deficiency on body mineral distribution has been studied almost exclusively in the liver, where the findings are surprisingly inconsistent. Reduced liver zinc concentrations were found in most animal studies [14][15][16], except that of Kilicalp et al [17] who showed no change. Whereas some authors have reported lower copper [15,16] concentrations in livers of protein-deficient rats, others have demonstrated no change of copper, manganese [17,18], calcium, and magnesium concentrations [17].…”
Section: Introductionmentioning
confidence: 93%
“…Reduced liver zinc concentrations were found in most animal studies [14][15][16], except that of Kilicalp et al [17] who showed no change. Whereas some authors have reported lower copper [15,16] concentrations in livers of protein-deficient rats, others have demonstrated no change of copper, manganese [17,18], calcium, and magnesium concentrations [17]. Higher liver iron concentrations have been detected in several studies [16][17][18], but one study reported no change [15].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation